Sedation and Analgesia in Children with Developmental Disabilities and Neurologic Disorders - Todd J. Kilbaugh; Stuart H. Friess; Ramesh Raghupathi; Jimmy W. Huh (International Journal of Pediatrics)
Sedation and analgesia performed by the pediatrician and pediatric subspecialists are becoming increasingly common for diagnostic and therapeutic purposes in children with developmental disabilities and neurologic disorders (autism, epilepsy, stroke, obstructive hydrocephalus, traumatic brain injury, intracranial hemorrhage, and hypoxic-ischemic encephalopathy). The overall objectives of this paper are (1) to provide an overview on recent studies that highlight the increased risk for respiratory complications following sedation and analgesia in children with developmental disabilities and neurologic disorders, (2) to provide a better understanding of sedatives and analgesic medications which are commonly used in children with developmental disabilities and neurologic disorders on the central nervous system.